Protecting the most vulnerable: Litigation from pediatric otolaryngologic procedures and conditions. (29th April 2014) - Rose, Christopher; Svider, Peter F.; Sheyn, Anthony; Meadows, Lila N.; Eloy, Jean Anderson; Coticchia, James; Folbe, Adam J.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To identify allegations raised in litigation stemming from pediatric otolaryngologic procedures and conditions. Study Design Retrospective analysis of a legal database. Methods The authors reviewed jury verdict and settlement reports on the WestlawNext database from 1994 to 2013 for cases involving pediatric plaintiffs and alleged negligence in otolaryngologic procedures and conditions. Results Of the 78 cases included, 52.6% were resolved with a payment; aggregate payments exceeded 69 million, and median jury‐awarded damages and settlements were 874, 190 and 250, 000, respectively. Adenotonsillectomy was the most commonly litigated procedure. Otolaryngologists were defendants in 42 (53.8%) cases, with pediatricians and anesthesiologists the next most commonly named defendants. Forty‐six (59.0%) cases involved alleged negligence in operative management, whereas other factors included permanent injury (44.9%), misdiagnosis/failure to diagnose in a timely manner (41.0%), death (35.9%), and requiring additional surgery. Airway‐related complications and allegedly permanent injuries significantly increased the size of payments. Awards were highest in cases with plaintiffs at 1 to 5‐years of age and lowest among children older than 10 years of age. Conclusions Unique considerations specific to pediatric patients are involved in malpractice litigation, and damages awarded were considerable. By including the specific factors listed in this analysis in a comprehensive informed consent process, and recognizing concerns specific to this patient population, practitioners in multiple specialties may potentially reduce liability. Clear communication with parents is a critical component of this process. Level of Evidence NA Laryngoscope, 124:2161–2166, 2014